Yahoo奇摩 網頁搜尋

  1. ...n3 are unknown[+s]. 乍看之下我們沒啥進展因為n1和n3是未知數. By using the equation of the orbital plane, we have at least reduced coefficients [+which]...

    分類:科學 > 數學 2009年09月13日

  2. Let y=f(x) =20 csc(x) be the length of the hypotenus. We have x0=30 degree= pi/6 (in radian); with a possible error...2*sqrt(3)*(pi/180) = (2sqrt(3)pi/9) centimeter, the maximum of the error. As to the percentage erron , by definition it is |delta y| divide by |y| at x=30 degree, so...

    分類:科學 > 數學 2009年11月21日

  3. 區域R: 0≦y≦2, y^2/4-1≦x≦1-y^2/4變成 uv-座標上的區域 R*.由 x=u^2-v^2, y=2uv, 代入 R 之描述, 得 R* 上之描述為: 0≦2uv≦2, (2uv)^2/4-1≦u^2-v^2≦1-(2uv)^2/4 等價於 0≦uv≦1, (uv)^2-1≦u^2-v^2≦1-(uv)^2 由 (uv)^2-1≦u^2-v^2 推出 v^2≦1, 由 u^2-v^2≦1-(uv)^2 推出 u^2≦1. 又, 由 u^2≦1, v^2...

    分類:科學 > 數學 2012年04月19日

  4. ...≧18]>17.5]. An airline has determined that 20% of its international flights are not on time. Use the normal approximation to the binomial distribution to answer the following questions...

    分類:科學 > 數學 2012年11月21日

  5. 2s/[s(s^2-3s+2)] =2/(s^2-3s+2) =2/[(s-1)(s-2)] = 2/(s-2) - 2/(s-1) so that, the inverse Laplace transform of 2s/[s(s^2-3s+2)] = L^(-1) { 2/(s-2) - 2/(s-1) } = 2 e^(2x) - 2 e^x

    分類:科學 > 數學 2011年07月15日

  6. ... V be a finite dimensional vector space of dimension n. I will use the fact that any linearly independent set of n vectors...b)s1 + ... + (ak/b)sk is a linear combination of the vectors in S, contradiction. Hence...

    分類:科學 > 數學 2006年07月21日

  7. F(x)=sinx, F(0)=0F (x)=cosx, F (0)=1F"(x)=-sinx, F"(0)=0F" (x)=-cosx, F" (0)=-1....F(x)=F(0)+F (0)x+[F"(0)/2!]x2+[F" (0)/3!]x3+...    =x-(1/6)x3+...F(0.1)=sin(0.1)=0.1-(1/6)*(0.1)3+...      ≒0.1-0...

    分類:科學 > 數學 2005年12月22日

  8. ...3=2/2y^2=1/y2=0-1=-1=converge 4. Find a " test integral " to be used in determining the convergence or divergence of the improper integral, and determine the convergence or divergence of the integral. W...

    分類:科學 > 數學 2012年10月16日

  9. 1+x+x^2+.. = 1/(1-x) for -1<x<1 differtiating it, then 1+2x+ 3x^2 + ... = 1/(1-x)^2 => x(1+2x+3x^2+ ...) = x/(1-x)^2 so, x+ 2x^2 + 3x^3+ ... = x/(1-x)^2

    分類:科學 > 數學 2009年02月20日

  10. Basic formula: L{1}= 1/s L{sin(ax)}= a/(s^2+a^2) L{cos(ax)}= s/(s^2+a^2) L{e^(ax)}= 1/(s-a) L{cosh(ax)}= s/(s^2-a^2) so that, a. L{3}= 3/s b. L{e^(2x)}= 1/(s-2) c. L{sin(2x)}= 2/(s^2+4) d. L{cosh(x)}= s/(s^2-1)

    分類:科學 > 數學 2011年07月15日